THE EFFECTS OF USING AUDIO-VISUAL LEARNING MEDIA ON THE STUDENTS LISTENING SKILL - Muh. Al Ikhsandi Palysa Putra; Kisman Salija; Amirullah Abduh (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The objective of this research was to find out whether or not the effect of using audio-visual media on the student’s listening skills. This research took place at SMA Negeri 2 Jeneponto. The population of this research was the tenth student of SMA Negeri 2 Jeneponto. The researchers used a listening test by using audio-visual media to collect the data. The instrument of this research was a multiple-choice written test which administer as a pre-test and post-test. Based on the result of the mean score, the researchers found that there are effects of using audio-visual learning media because the result of the post-test was higher than the result of the pre-test (64.33 > 43.50). Then, the researchers conclude that the effect of using audio-visual learning media on the student’s listening skills at SMA Negeri 2 Jeneponto academic year 2022/2023.